Neue Klasse von Methyltransferasen mit Zyklisierungsaktivität - Birgit Piechulla; Nancy Magnus; Marie Chantal Lemfack; Stephan Von Reuss (BIOspektrum, 2021)
Microorganisms release small volatile metabolites with unique structures, e. g. the polymethylated homosesquiterpene sodorifen from Serratia plymuthica . Two unusual enzymes with novel features are involved in its biosynthesis, a C -methyltransferase with cyclization activity and a terpene synthase that accepts a non-canonical monocyclic C 16 substrate. The novel class of methyltransferases represents an alternative route that enlarges terpene diversity.

Characteristic alatoid ‘cineole cassette’ monoterpene synthase present in Nicotiana noctiflora - Anke Fähnrich; Madeleine Neumann; Birgit Piechulla (Plant Molecular Biology, 2014)

Professorinnen — Hürden und Chancen - Birgit Piechulla (BIOspektrum, 2012)

Synthesis of ‘cineole cassette’ monoterpenes in Nicotiana section Alatae: gene isolation, expression, functional characterization and phylogenetic analysis - Anke Fähnrich; Anne Brosemann; Laura Teske; Madeleine Neumann; Birgit Piechulla (Plant Molecular Biology, 2012)

Volatile Mediated Interactions Between Bacteria and Fungi in the Soil - Uta Effmert; Janine Kalderás; René Warnke; Birgit Piechulla (Journal of Chemical Ecology, 2012)

Belowground volatiles facilitate interactions between plant roots and soil organisms - Katrin Wenke; Marco Kai; Birgit Piechulla (Planta, 2010)

Enzymatic, expression and structural divergences among carboxyl O-methyltransferases after gene duplication and speciation in Nicotiana - Frank Hippauf; Elke Michalsky; Ruiqi Huang; Robert Preissner; Todd J. Barkman; Birgit Piechulla (Plant Molecular Biology, 2010)

SAM levels, gene expression of SAM synthetase, methionine synthase and ACC oxidase, and ethylene emission from N. suaveolens flowers - Susanna Roeder; Katharina Dreschler; Markus Wirtz; Simona M. Cristescu; Frans J. M. van Harren; Rüdiger Hell; Birgit Piechulla (Plant Molecular Biology, 2009)

Regulation of simultaneous synthesis of floral scent terpenoids by the 1,8-cineole synthase of Nicotiana suaveolens - Susanna Roeder; Anna-Maria Hartmann; Uta Effmert; Birgit Piechulla (Plant Molecular Biology, 2007)

Volatiles of bacterial antagonists inhibit mycelial growth of the plant pathogen Rhizoctonia solani - Marco Kai; Uta Effmert; Gabriele Berg; Birgit Piechulla (Archives of Microbiology, 2007)

Plant scents ? mediators of inter- and intraorganismic communication - Birgit Piechulla; Marcella B. Pott (Planta, 2003)

Identification of tomato Lhc promoter regions necessary for circadian expression - Birgit Piechulla; Nicole Merforth; Barbara Rudolph (Plant Molecular Biology, 1998)